Eccentrics 21 stories of unusual and remarkable people: with exercises for developing critical reading skills (Critical reading series, 1999)
Nonfiction articles profiling Snowflake Bentley, Black Bart, George Kaufman, Doris Duke, Johnny Appleseed, Diamond Jim Brady, Lillie Hitchcock Coit, Bill Veeck, Gertrude Lintz, Hetty Green, Alan Abel, Ludwig II, Salvador Dali, Sun Ra, Norton I, Carry Nation, Vincent van Gogh, Amanda Feilding, Ferdinand Demara, Dennis Rodman, and Imelda Marcos. Each is followed by reading comprehension and critical thinking exercises.